2021
DOI: 10.1001/jamanetworkopen.2020.36304
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Between Non–vitamin K Antagonist Oral Anticoagulants and Low-Molecular-Weight Heparin in Asian Individuals With Cancer-Associated Venous Thromboembolism

Abstract: This cohort study compares the risks of venous thromboembolism (VTE) recurrence in patients receiving non–vitamin K antagonist oral anticoagulants (NOACs) vs low-molecular-weight heparin in Asian individuals with cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
48
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(76 citation statements)
references
References 32 publications
8
48
3
Order By: Relevance
“…In this study, the majority of patients were female (66.2%). These findings seem to be interesting since other studies showed similar percentages of male and female patients (Young et al, 2018;Faqah et al, 2020;Chen et al, 2021). Countless risk factors for CAT have been narrated well in literature (Ay et al, 2017;Abdol Razak et al, 2018).…”
Section: Discussionsupporting
confidence: 73%
“…In this study, the majority of patients were female (66.2%). These findings seem to be interesting since other studies showed similar percentages of male and female patients (Young et al, 2018;Faqah et al, 2020;Chen et al, 2021). Countless risk factors for CAT have been narrated well in literature (Ay et al, 2017;Abdol Razak et al, 2018).…”
Section: Discussionsupporting
confidence: 73%
“…MB events are very burdensome and frequently severely disabling, leading to low QALYs despite it is modest decrease. Recent studies found that DOACs may be associated with low MB events for the treatment of cancer-associated VTE in Asian patients than in non-Asian patients [ 56 ]. Furthermore, a significant decrease in GI bleeding risk was observed with DOACs [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies found that DOACs may be associated with low MB events for the treatment of cancer-associated VTE in Asian patients than in non-Asian patients [ 56 ]. Furthermore, a significant decrease in GI bleeding risk was observed with DOACs [ 56 ]. So DOACs can be a more cost-effective treatment compared to LMWHs in Chinese patients with CAT.…”
Section: Discussionmentioning
confidence: 99%
“…This study analyzed data from the Chang Gung Research Database (CGRD), which is a multi-institutional medical records database of the CGMH system [ 6 , 7 ]. The CGMH system has been described previously [8] . In brief, it includes seven branches (four tertiary academic medical centers and three teaching hospitals) across Taiwan, with a total of 10,050 beds and 2.4 million hospitalizations every year.…”
Section: Methodsmentioning
confidence: 99%